Biomass to renewable energy processes - Cheng, Jay; CRC Press (Boca Raton, FL : CRC Press, 2017)
Biomass to Renewable Energy Processes, Second Edition, explains the theories of biological processes, biomass materials and logistics, and conversion technologies for bioenergy products such as biogas, ethanol, butanol, biodiesel, and synthetic gases. The book discusses anaerobic digestion of waste materials for biogas and hydrogen production, bioethanol and biobutanol production from starch and cellulose, and biodiesel production from plant oils. It addresses thermal processes, including gasification and pyrolysis of agricultural residues and woody biomass. The text also covers pretreatment technologies, enzymatic reactions, fermentation, and microbiological metabolisms and pathways.
chapter 1 Introduction / Jay J. Cheng -- chapter 2 Biomass Chemistry / Deepak R. Keshwani -- chapter 3 Biomass Resources / Wenqiao Yuan -- chapter 4 Biomass Logistics / Matthew W. Veal -- chapter 5 Kinetics and Microbiology of Biological Processes / Jay J. Cheng -- chapter 6 Anaerobic Digestion for Biogas Production / Jay J. Cheng -- chapter 7 Biological Process for Ethanol Production / Jay J. Cheng -- chapter 8 Biological Process for Butanol Production / Maurycy Daroch -- chapter 9 Chemical Conversion Process for Biodiesel Production / Wenqiao Yuan -- chapter 10 Thermochemical Conversion of Biomass to Power and Fuels / Hasan Jameel.
Keywords: Biomass energy; Renewable energy sources